Polyploidy Induction of Rutaceae through Bio-catharanthine Treatment - Aziz, Isna Rasdianah; Muthiadin, Cut; Hajrah, Hajrah; Alir, Rahmat Fajrin; Suryafly, Fanny Dhea; Amnah, Alifah Zul; Hermawan, Isna Ainun; Mustami, Muhammad Khalifah; Mahfut, Mahfut; Upreti, Brij Mohan (Biota, 2021)
Indonesia has a tropical monsoon-type climate which suitable for agriculture and plantations. One of the main centers of orange fruits (Citrus sp.) production in Indonesia and become the top ten with the largest production is in South Sulawesi. Farmers commonly cultivate siam oranges (Citrus nobilis). Lime (Citrus aurantifolia) has not yet become the main production, which is inversely proportional to the high demand in South Sulawesi. This study aims to determine the ability of bio-catharanthine as a polyploidy agent against the phenotype of the familia Rutaceae cultivated in South Sulawesi. The research was carried out in Laboratory of Genetics and Molecular Biology, Department of Biology, Universitas Islam Negeri Alauddin Makassar using randomized complete block design consisted of two conditions (bio-catharanthine concentration including C1 = Bio-catharanthine 0.05%; C2 = Bio-catharanthine 0.075%; C3 = Bio-catharanthine 0.1% and immersion time including T1 = 3 h; T2 = 6 h). Phenotypic observations include plant height, the number of leaves and nodes, the length of roots, and the number of roots per shoot. The results of the study showed that the bio-catharanthine immersion of 0.05-0.075% for 6 hours in Rutaceae had a significant effect on their phenotypic characters.